2020
DOI: 10.1002/ijgo.13331
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of noncommunicable diseases by interventions in the preconception period: A FIGO position paper for action by healthcare practitioners

Abstract: With the increase in obesity prevalence among women of reproductive age globally, the risks of type 2 diabetes, gestational diabetes, pre‐eclampsia, and other conditions are rising, with detrimental effects on maternal and newborn health. The period before pregnancy is increasingly recognized as crucial for addressing weight management and reducing malnutrition (both under‐ and overnutrition) in both parents to reduce the risk of noncommunicable diseases (NCDs) in the mother as well as the passage of risk to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 67 publications
(84 reference statements)
1
64
1
1
Order By: Relevance
“…It has paramount importance to reduce NCDs by providing an opportunity to early optimizing the health of potential mothers and couples [ 31 , 32 ]. The World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), and International Federation of Gynecology and Obstetrics (FIGO) recommends the need for women to screen for NCDs before conception which helps for early identification of the diseases, management, and reducing its consequences [ 31 , 33 , 34 ]. There are also evidences of the effectiveness of preconception care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has paramount importance to reduce NCDs by providing an opportunity to early optimizing the health of potential mothers and couples [ 31 , 32 ]. The World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), and International Federation of Gynecology and Obstetrics (FIGO) recommends the need for women to screen for NCDs before conception which helps for early identification of the diseases, management, and reducing its consequences [ 31 , 33 , 34 ]. There are also evidences of the effectiveness of preconception care.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a systematic review and meta-analysis from Pakistan indicated that maternal diabetic care during preconception period reduces the occurrence of congenital malformations by 70% and perinatal mortality by 69% [ 35 ]. However, despite its importance and recommendations [ 31 , 33 , 34 ], to the best of the authors’ knowledge, there are no published articles on awareness of NCDs screening during the preconception period in Ethiopia. Therefore, this study aimed to assess women’s awareness of common NCDs screening during the preconception period and associated factors in Manna district, Jimma Zone, Oromia region, Ethiopia, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Resources, such as the FIGO Nutrition Checklist, are available to health care practitioners to identify and address nutrition and weight issues before and during pregnancy. 76,77 A preconception risk assessment by health care professionals may identify women with preexisting diabetes, and also identify women at risk of GDM. 78 Risk assessment tools have shown nulliparous women at risk of GDM may be accurately identified before pregnancy based on a set of easily obtainable lifestyle and health-related characteristics 79,80 ; however, further research is needed to determine if preconception risk identification is acceptable and if model implementation followed by targeted preconception care reduces rates of GDM.…”
Section: Pre-and Interconception Interventionsmentioning
confidence: 99%
“…81,82 In addition to provision of preconception care among women planning for pregnancy, a universal approach of discussing dietary habits, risks of obesity, and potential benefits of weight loss prior to pregnancy at every contact with a healthcare practitioner is recommended. 77…”
Section: Pre-and Interconception Interventionsmentioning
confidence: 99%
See 1 more Smart Citation